2023
DOI: 10.3390/su15043478
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment of Chinese Tourists towards Malaysia Cultural Heritage Based on Online Travel Reviews

Abstract: Analyzing the perception differences and influencing factors of cross-cultural groups in heritage tourism can help heritage sites to formulate differentiated service and improve tourist satisfaction. This research adopted the BERT model to undertake sentiment analysis of 17,555 Chinese online reviews for nine scenic spots in Melaka. Using vocabulary filtering, co-occurrence analysis, and semantic clustering technology, the emotional characteristics of Chinese outbound tourists when they visited heritage sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Figure 8 depicts the performance of the proposed MQ-LSTM-based RS with existing systems developed by [23,24,26]. From the analysis, it is clear that by obtaining a high RR of 97.22%, the proposed model exhibited superior performance.…”
Section: Performance Analysis Of the Recommendation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 depicts the performance of the proposed MQ-LSTM-based RS with existing systems developed by [23,24,26]. From the analysis, it is clear that by obtaining a high RR of 97.22%, the proposed model exhibited superior performance.…”
Section: Performance Analysis Of the Recommendation Systemmentioning
confidence: 99%
“…However, with fuzzy logic, inappropriate decision-making rules would deteriorate the assessment results. [26] recommended a model for the sentiment analysis of Chinese tourists toward Malaysia's cultural heritage grounded on online travel reviews. The sentiment analysis leveraged vocabulary filtering, semantic clustering technology, and BERT, along with co-occurrence analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Duan et al [47] used Bert instead of Word2vec extracted word vector as the model input, improving text classification's effect. Cao et al used the Bert model to analyze the sentiment of online reviews of nine attractions in Melaka, and the results showed that the BERT-based deep learning approach can obtain improved sentiment predictive performance [7]. Deep learning-based models have significant advantages over the first two approaches in that they can process complex, large-scale information more efficiently.…”
Section: Research On Text Sentiment Analysis Techniquesmentioning
confidence: 99%
“…Deep learning, as a branch in the field of machine learning, is capable of acquiring high-level features from data, digging deeper into the perceived elements of a destination's image, and focusing on the deeper information behind the emotional changes of travelers when experiencing a destination. Currently, scholars have paid attention to the application of deep learning models such as LSTM [6], Bert [7], and CNN [8] on image perception of tourist destinations and confirmed the advantages of deep learning models in processing tourist review texts. Tourism review texts may contain content unrelated to the destination image, which may affect our understanding of the destination image, which will be a difficulty and a challenge when we study the destination image.…”
Section: Introductionmentioning
confidence: 99%